Test The Activity of Microgel Preparations from Skin Extract Jengkol (Pithecellobium lobatum Benth) on The Healing of Cut Wounds in White Rats (Rattus novergicus) - Utama, Rezza Fikrih; Situmorang, Renni Paska; Husaini, Fahri; Andry, Muhammad; Wijayanti, Fitria Eka Resti (Jurnal Biologi Tropis, 2024)
The skin is the largest and heaviest organ in the body, covering its outer surface. Wounds are often experienced by everyone due to the loss of epithelial integrity of the skin. Jengkol fruit skin is useful as a burn medicine and antiseptic to test the activity of microgel preparations from jengkol skin extract (Pithecellobium lobatum Benth) on healing cuts in white rats (Rattus novergicus). This study was a true experimental, post test control only design using the Completely Randomized Design (CRD) statistical method. The data were analyzed statistically using SPSS and continued with ANOVA test to see significant differences between the 5 treatment groups. The results of the study obtained microgel preparations that had activity for healing cuts on the backs of white rats, namely the F3 preparation with a concentration of 15% jengkol skin extract with wound observation for 12 days. In conclusion, cuts on the backs of white rats can be healed with jengkol skin extract.